Association of intracranial arteriovenous malformation embolization with more rapid rate of perfusion in the peri-nidal region on color-coded quantitative digital subtraction angiography. (18th March 2020) - Shellikeri, Sphoorti; Bai, Harrison; Setser, Randolph M; Hurst, Robert W; Cahill, Anne Marie
Abstract : Background: Hemodynamic alterations post-embolization of intracranial arteriovenous malformations (AVMs) may cause delayed edema/hemorrhage in brain parenchyma adjacent to the lesion. Objective: To quantify and compare cerebral perfusion changes in the peri-AVM territory pre- and post-embolization using color-coded quantitative digital subtraction angiography (q-DSA). Methods: Pediatric intracranial AVM embolization procedures performed over a 5 year period were included. DSA images of all patients were retrospectively assessed using syngo iFlow. Regions of interest (ROI) were selected on anteroposterior and lateral q-DSA views: three in the peri-AVM region; two in parenchyma distant from the AVM. Time-to-peak (TTP) contrast enhancement of ROIs and ∆TTP (TTP at the selected ROI minus TTP at either the ipsilateral internal carotid/vertebral artery) were measured. Result: 19 pediatric patients with 19 AVMs (9 males/10 females, mean age 12 years) underwent intracranial AVM embolization: 15/19 AVMs were supplied by the anterior circulation and 4/19 by the posterior circulation. Blood flow was significantly slower post-embolization in the draining vein (19/19) (p<0.01), and the venous sinus outflow (17/19) (p<0.01), by mean difference of 2.01±1.31 s and 1.74±2.04 s. There was significantly increased peri-AVM parenchymal perfusion post-embolization (∆TTP=2.20±0.48 s) compared with pre-embolization (∆TTP=2.52±0.42 s), by an average ∆TTP of 0.33±0.53 s (p=0.014). In contrast, there was no perfusion difference (∆TTP=0.03±0.20 s, p=0.8) between pre- and post-embolization in the distant parenchyma. The size of the AVM was not correlated with change in peri-nidal parenchymal perfusion (r=−0.136, p=0.579). Conclusion: This study demonstrates more rapid perfusion in the peri-nidal brain parenchyma post-embolization of the AVM, which supports the theory that increased perfusion in normal tissue surrounding the AVM after embolization may underlie some post-procedural complications.